Biosimilar formulary placement in Medicare Part D prescription drug plans: A case study of infliximab. (8th December 2020) - Socal, Mariana P; Ezebilo, Ijeamaka; Bai, Ge; Anderson, Gerard F
Abstract: Purpose: Biosimilars can generate competition and provide cost savings over reference biologics for the Medicare program and beneficiaries. The extent to which these benefits can be realized in the Medicare Part D program depends on how biosimilars and biologics are placed in the formulary. We conducted a study to examine Medicare formulary placement of the first biologic to have 2 biosimilars on the market—infliximab and its biosimilars infliximab-dyyb and infliximab-abda. Methods: All standalone and Medicare Advantage (MA) prescription drug plans (PDPs) offered in Medicare Part D were examined between September 2016 (ie, at the end of the last quarter before the launch of the first infliximab biosimilar) and September 2018, at which time a second biosimilar had been on the market for about 14 months. When PDPs covered both the reference biologic and a biosimilar, we compared the cost-sharing tier and the frequency of prior authorization and step therapy requirements for each drug. Results: Nearly all PDPs covered infliximab throughout the study period. By September 2018, 31.7% of MA plans and 14.9% of standalone PDPs were covering a biosimilar on the market. Nearly all plans that covered a biosimilar also covered the reference product. Most plans (98% of standalone PDPs and 89% of MA plans) had placed prior authorization restrictions on both the biologic and the biosimilar. All plans covering both products placed them in the same cost-sharing tier. No plan required step therapy for either product. Conclusion: Formulary placement of infliximab biologic and biosimilars in Medicare Part D is not optimized to generate cost savings for the Medicare program and beneficiaries, whose cost sharing is often based on the drug's list price. The Medicare program should provide incentives for PDPs to expand biosimilar coverage.